Beyond Godisa: critical success factors for business incubators in South Africa - Kavhumbura, Vimbainashe O. (My University, 2015)
This study examined the critical success factors of small business development organisations and business incubators in South Africa. Toplevel managers and directors of these organisations were surveyed both on the characteristics of their organisations and on their perceptions of critical success factors as identified by Buys and Mbewana (2007) in a previous study of a similar nature. The researcher sought to establish whether these pre-defined antecedents of incubator success were still relevant to the current South African context and if the business model of the organisation had any bearing on performance outcomes. Some critical success factors, namely Access to Technical Expertise, Supportive Government Policy, Availability of Funding and Management Competencies were found to have no significant relationship with incubator performance, while Networking, Stakeholder Support, Financial Sustainability and Stringent Selection Criteria were positively correlated to the performance of the organisation. These outcomes of the quantitative survey were then explored in more detail through three in-depth interviews with directors of organisations with different priority goals and different small business development models.
Thesis (M.M. (Entrepreneurship and New Venture Creation))--University of the Witwatersrand, Faculty of Commerce, Law and Management, Graduate School of Business Administration, 2014.